A Brief Report of the Federal Government of Canada's Residential School System for Inuit - David King (Aboriginal Healing Foundation, 2006)
This report summarizes the federal government's involvement in Inuit education as reported by David King in an earlier report for the Aboriginal Healing Foundation.